Language impact on productivity for industrial end users: A case study from Programmable Logic Controllers - Fronchetti, Felipe; Ritschel, Nico; Holmes, Reid; Li, Linxi; Soto, Mauricio; Jetley, Raoul; Wiese, Igor; Shepherd, David (Journal of computer languages (Online), 2022)
Industrial workplaces increasingly require end-users to create programs for embedded systems, but little expert scrutiny has been devoted to studying this domain. As a result, industrial end-user programmers may rely on programming languages and development environments that do not necessarily follow the state-of-the-art of software engineering. Consider Ladder Logic, the most popular language used to program the most widely deployed type of industrial hardware, programmable logic controllers (PLCs). Ladder Logic’s fundamental design is based on electric relay circuits that have long since disappeared from practice. Does Ladder Logic inhibit the productivity of end-user programmers, slowing progress in industrial settings like manufacturing sites and scientific labs where it is widely used? To better understand the usage of domain-specific languages in industrial practices, we conducted a survey with 175 technical employees from an international engineering conglomerate. This survey introduced participants to Ladder Logic and asked them questions that all programmers, including novices, should answer with ease. Nearly 70% failed, including those with previous Ladder Logic experience. We combined end-user performance with answers in an open-ended question, where many employees complained about the programming language. The breadth and depth of these struggles suggest that outdated languages, which industrial end users must increasingly use, could dramatically impact productivity and that further studies on these industrial end user programmers be necessary to better support them in their increasingly complex workplaces.